INVESTIGATION TOWARDS THE LONG-RUN PERFORMANCE OF INITIAL PUBLIC OFFERINGS: EVIDENCE FROM INDONESIAN CAPITAL MARKET - Lioniva Emasari; Dewi Tamara (Bina Nusantara University, 2010)
We study the long-term performance of IPO share issued in Indonesia during the 1996-2001 periods. The IPOs in this period are mostly concentrated in Finance, Trade, Property and Basic Industry & Chemicals. The cumulative abnormal return (CAR) and buy-and-hold abnormal return (BHAR) in the third year are 15.83% and negative 68.02%, respectively. The CAR and BHAR in the fifth year are negative 1% and negative 139.7%, respectively. The highest CAR for 3 and 5 years are mining industry, with 289.29% and 226.80%, respectively. The lowest CAR for third year is trade, service & investment industry, with negative 59.36% and fifth year is agriculture with negative 59.72%. The lowest BHAR for third and fifth year is trade, service and investment industry with negative 113.01% and negative 230.99 respectively. The long-run performance using cumulative abnormal return is similar with the market and cannot outperform the market.